Business ethics - Jennings, Marianne (Thomson/South-Western West, 2003)
Previous ed.: Cincinnati, Ohio : West Educational, 1999.; BUSINESS ETHICS: CASE STUDIES AND SELECTED READINGS, 6th Edition explores the complex issues of ethics from the inside. Offering a unique perspective, this market-leading text gets behind the decision-making process of today's business leaders -- from prominent players to everyday professionals. It helps you dissect what makes people cross lines they would not ordinarily cross. A combination of short and long cases, readings, hypothetical situations, and current ethical dilemmas, BUSINESS ETHICS provides a thorough training and thought-provoking experience on business ethics. Applying theory to real-world practice, it reinforces a vital sense of values in future business leaders; Includes bibliographical references and index